University Student Engagement Inventory (USEI): Transcultural Validity Evidence Across Four Continents - Assunção, Hugo; Lin, Su-Wei; Sit, Pou-Seong; Cheung, Kwok-Cheung; Harju-Luukkainen, Heidi; Smith, Thomas; Maloa, Benvindo; Campos, Juliana Álvares Duarte Bonini; Ilic, Ivana Stepanovic; Esposito, Giovanna; Francesca, Freda Maria; Marôco, João (Frontiers in Psychology, 2020)
Abstract Academic engagement describes students’ involvement in academic learning and achievement. This paper reports the psychometric properties of the University Student Engagement Inventory (USEI) with a sample of 3992 university students from nine different countries and regions from Europe, North and South America, Africa, and Asia. The USEI operationalizes a trifactorial conceptualization of academic engagement (behavioral, emotional and cognitive). Construct validity was assessed by means of confirmatory factor analysis and reliability was assessed using Cronbach’s alpha and McDonald’s omega coefficients. Weak measurement invariance was observed for country/region, while strong measurement invariance was observed for gender and area of graduation. The USEI scores showed predictive validity for dropout intention, self-rated academic performance, and course approval rate while divergent validity with student burnout scores was also evident. Overall, the results indicate that the USEI can produce reliable and valid data on academic engagement of university students across the world.